Transkrypcja jako działanie interpretacyjne = Transcription as interpretative activity - Bielecka-Prus, Joanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The main theses: 1. Transcription of data (audio and visual) is a part of research practice subject to weak afterthought. 2. Transcription is an interpretative act, not the projection of data. This act may be influenced by varied social and cultural factors.
Keywords: transkrypcja; badania jakościowe